TRANSPLANTASI TUBUH DALAM TINJAUAN HUKUM ISLAM - Abdurrahman Kasdi (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2013)
According to Islam, men should carry out all activities in life in line with God's commands and His prohibitions. In addition, consideration is taken with respect to maslahat or mafsadat, also pay attention to the benefits obtained or loss that may befall. Paradigms of thinking established in fiqh concerning transplantation are: first, human organs are honorable, whether the man is still alive or dead. Second, human dignity is classified according to the ideology of citizens who prevailed at the time. These are Muslim citizen, dhimmi citizen, harbi citizen, and apostate citizens. This paradigm influences the decision in fiqh. In the context of fiqh, there are several legal opinions of scholars regarding organ transplants in terms of the state of the donor, ie: donating organs of a living person, in a coma donation, donate deceased organs, and transplantation of different religions.Keywords: Transplants, Organ, Donor, Fiqh, Maslahat, Mafsadat